An unusual overrepresentation of genetic factors related to iron homeostasis in the genome of the fluorescent Pseudomonas sp. ABC1 - Valenzuela-Heredia, Daniel; Henriquez-Castillo, Carlos; Donoso, Raul; Lavin, Paris; Ringel, Michael T.; Bruser, Thomas; Campos, Jose Luis (My University, 2021)
Members of the genus Pseudomonas inhabit diverse environments, such as soil, water, plants and humans. The variability of habitats is reflected in the diversity of the structure and composition of their genomes. This cosmopolitan bacterial genus includes species of biotechnological, medical and environmental importance. In this study, we report on the most relevant genomic characteristics of Pseudomonas sp. strain ABC1, a siderophore-producing fluorescent strain recently isolated from soil. Phylogenomic analyses revealed that this strain corresponds to a novel species forming a sister clade of the recently proposed Pseudomonas kirkiae. The genomic information reveals an overrepresented repertoire of mechanisms to hoard iron when compared to related strains, including a high representation of fecI-fecR family genes related to iron regulation and acquisition. The genome of the Pseudomonas sp. ABC1 contains the genes for non-ribosomal peptide synthetases (NRPSs) of a novel putative Azotobacter-related pyoverdine-type siderophore, a yersiniabactin-type siderophore and an antimicrobial betalactone; the last two are found only in a limited number of Pseudomonas genomes. Strain ABC1 can produce siderophores in a low-cost medium, and the supernatants from cultures of this strain promote plant growth, highlighting their biotechnological potential as a sustainable industrial microorganism.
Keywords: Pyoverdine; Strain (injury)